Evaluation of an Antifouling Surface Inspired by Malaysian Sharks Negaprion Brevirostris and Carcharhinus Leucas Riblets - Mohd Danial, Ibrahim; Philip, Susan; Lam, Su Shiung; Sunami, Yuta (Japanese Society of Tribologists, 2021)
Our research aims to study the properties of real shark skin in accordance with its topographical features and the biomimicry for friction reduction. In this paper, we are focusing on antifouling surface modification based on the surface roughness and frictional resistance inspired from the shark’s denticule arrangements. Biomimetic shark skins were prepared using the silicone laminated transfer molding method to investigate the antifouling effects. Anti-algae formations were investigated to examine and assess the antifouling properties of the biomimetic shark skin surface microstructure. The results indicated that the effect of microreplication with shark skin on the surface had reduced 13% - 40% of algae formation. The characteristics of the hydrophobic properties for shark skin had also been investigated through the analysis of the contact angle (CA). Scanning electron microscopy (SEM) is used to observe the surfaces morphologies of the shark skin as well as the biomimetic shark skin. In addition to that, the frictional resistance experiment was carried out to evaluate the friction of coefficient (COF) of different surface modifications. The frictional resistance experiment for real shark skin and replicated shark skin demonstrated lowered COF value ranging from μ= 0 to 1, compared to the COF for controlled surface whereby the value ranges from μ= 0 to 5.